MINT pilot study : a text message package as an adjunct to existing mindfulness-based cognitive therapy in an early intervention setting : a thesis presented in partial fulfilment of the requirements of the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Miller, Mary (Massey University, 2018)
Background: Mindfulness-Based Cognitive Therapy (MBCT) is being used in an increasing number of settings including Early Intervention (EI) for psychosis services. People with psychotic symptoms face difficulties including compliance problems with home-based practice, which may affect the utility of MBCT. This study aimed to examine whether text message technology could be used as an adjunct to support home-based practice. Method: A single case multiple baseline design was used to assess the mindfulness text message intervention (MINT) in 11 participants. Results: There was a statistically significant increase of group mean total practice time per week of 7.1 minutes from the baseline to post-intervention phase, with a medium effect size. There were no statistically significant results for change in mindfulness skills or depression and anxiety symptoms. Discussion: Text messages can be used as an adjunct to support home-based practice in an EI setting. The amount of home-based practice required to produce an improvement in clinical outcomes is unclear. Future studies may explore the variation between participants found and the use of MINT in other settings.
Keywords: Mindfulness-based cognitive therapy; Psychoses; Patients; Services for; Mentally ill; Home care; Text messages (Cell phone systems); Health aspects; Crisis intervention (Mental health services); Evaluation